2019
DOI: 10.1155/2019/5315376
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Functional and Traditional Exercise on the Body Composition and Determinants of Physical Fitness of Older Women: A Randomized Crossover Trial

Abstract: Aim To analyze the efficacy of functional training (FT) and traditional training (TT) in body composition and determinants of physical fitness in older women. Methods This is a randomized clinical trial in which participants performed two 12-week periods of different training methods, separated by eight weeks of washout. Forty-eight physically active older women (≥60 years of age) completed the intervention in three groups: (i) program that started with FT and ended with TT (FT ⟶ TT: n = 19), (ii) program that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 36 publications
2
14
0
3
Order By: Relevance
“…Regarding the body composition, our results indicated significant changes in body fat percentage and lean body mass in both groups, but the difference between the groups was non-significant in terms of these parameters. This result is consistent with that of a previous study ( de Resende-Neto et al, 2019a ). Several studies have demonstrated the efficiency of resistance training in neuromuscular and metabolic stimulation to endorse tissue structure changes, such as reduced adipose and increased muscle tissues ( Hunter et al, 2013 ; Marín-Cascales et al, 2018 ).…”
Section: Discussionsupporting
confidence: 94%
“…Regarding the body composition, our results indicated significant changes in body fat percentage and lean body mass in both groups, but the difference between the groups was non-significant in terms of these parameters. This result is consistent with that of a previous study ( de Resende-Neto et al, 2019a ). Several studies have demonstrated the efficiency of resistance training in neuromuscular and metabolic stimulation to endorse tissue structure changes, such as reduced adipose and increased muscle tissues ( Hunter et al, 2013 ; Marín-Cascales et al, 2018 ).…”
Section: Discussionsupporting
confidence: 94%
“…Regarding the body composition, our results indicated signi cant changes in body fat percentage and lean body mass between the groups, although the difference between the groups was nonsigni cant in terms of these parameters. This result is consistent with that of a previous study [42]. Several studies have demonstrated the e ciency of resistance training in neuromuscular and metabolic stimulation to endorse tissue structure changes such as reduced adipose and muscle tissues [43,44].…”
Section: Quantifying Internal Training Loadsupporting
confidence: 92%
“…Además, el estudio de De Resende et al (2019a) donde fueron evaluados dos grupos (EFZA y EF), para el grupo EFZA se constató un aumentos significativo en la masa magra, y en el grupo EF hubo disminución significativa en el % de grasa, resultados que son semejantes a los encontrados en la presente investigación con EMC, teniendo en cuenta que en esta, fueron usados los dos métodos EFZA + EF junto a las amortiguaciones de las caídas del EJA (Tabla 2).…”
Section: Discussionunclassified
“…Se resaltan todavía otros hallazgos, como en el estudio de Cassemiro et al (2017) Cabe resaltar, que además de los métodos de entrenamiento utilizados EFZA y EF en este estudio, que ya están descritos ampliamente en la literatura demostrando su eficacia en la mejora en las múltiples variables de la salud (Cassemiro et al, 2017, Guedes et al, 2016, Heubel et al, 2018, De Resende et al, 2019a, también fue usado de forma innovadora, la inclusión del método EJA, en el cual (Borba et al, 2013a;2013b;, presentaron el EJA como alternativa en la protección contra caídas en mujeres en edad avanzada, mostrando mejoras en el desempeño del equilibrio, fuerza muscular, mantenimiento de la densidad mineral ósea y la calidad de vida comparado al GC.…”
Section: Discussionunclassified
See 1 more Smart Citation